RECEPTION OF FOREIGN AMBASSADORS IN THE KOKAND KHANATE: TRADITIONS AND PECULIARITIES (Scientific journal of the Fergana State University, 2023)
The article highlights the issues of ceremonial meeting and reception of foreign diplomatic missions in the Kokand Khanate. The article is based on the data of the authors of local essays and unique sources - “Safarnoma”.